(untitled) (Revista LIDER, 2020)
The article deals with a theoreticalempirical and critical in nature analysis of the new regionalism (NR) approaches that dominate the perspective of regional development throughout the last two decades. The capacity of such approaches to act as effective instruments is questioned not only in the analysis of the restrictions over the peripheral localities, but also in the formulation of public policies that make feasible a reversion of such positioning in the Latin American scenario. To support this critical hypothesis, we make use of a case study centered in Sarandi, a peripheral locality in the state ofRio Grande do Sul(Brazil).The intention is to show the contributions and, afterwards, the restrictions those emerging NR elements present when offering a consistent solution to the peripheral environments when confronting the challenge of their insertion in the chains of global values (CVG). We maintain that the NR restrictions result, essentially, from the use of an analytical scheme that impedes considering the importance of the “interweaving multiscalarity” of the current capitalistic restructuring process in which, indeed, the socio-economical dynamics and the institutional/state ones that take place in national spaces play a fundamental role, both in the elaboration of precise and contextualizing diagnostics of the local and meso-regional realities, and in the exploration of strategies capable of reverting the NR weaknesses and promoting an integrated development that includes the peripheral regions.